2017
DOI: 10.3892/etm.2017.5105
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus raises in vitro anticancer effect of geniposide in HSC‑3 human oral squamous cell carcinoma cells

Abstract: Abstract. The present study determined the ability of the Lactobacillus rhamnosus GG strain (LGG) to enhance the anticancer effects of geniposide on HSC-3 human oral squamous carcinoma cells.LGG (1.0x10 3 CFU/ml) on its own had no impact on human oral keratinocytes and HSC-3 cancer cells. Geniposide (25 or 50 µg/ml) had no impact on human oral keratinocytes, but exerted growth inhibitory effects on HSC-3 cancer cells, which were increased in the presence of LGG. Flow cytometric analysis and a nuclear staining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…In addition to cervical cancer, Lactobacillus is associated with the proliferation and regulation of cells of other cancer types, such as breast cancer, 32 colorectal cancer, 33 gastric cancer, 34 and oral cancer. 35 , 36 Observations in these other cancers may offer insights into the study of Lactobacillus in cervical cancer. The main observations regarding Lactobacillus in cancers are as follows: 1) Lactobacillus can activate and strengthen the antitumor effects of immunocytes such as thymus-derived cells (T cells), natural killer (NK) cells, dendritic cells (DCs), and macrophages and immunological factors produced by immunocytes; 37 – 39 2) a large amount of unmethylated dinucleotide repeat sequences present in the nuclei of Lactobacillus can activate the innate immune response by binding to a specific receptor that exists on the surface of human cells; 40 3) Lactobacillus that is suitable for reproduction and growth in an anaerobic environment can selectively accumulate in the hypoxic zones of solid cancers; 41 and 4) Lactobacillus can selectively locate to solid cancers and can be used as a vector for gene therapy and targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cervical cancer, Lactobacillus is associated with the proliferation and regulation of cells of other cancer types, such as breast cancer, 32 colorectal cancer, 33 gastric cancer, 34 and oral cancer. 35 , 36 Observations in these other cancers may offer insights into the study of Lactobacillus in cervical cancer. The main observations regarding Lactobacillus in cancers are as follows: 1) Lactobacillus can activate and strengthen the antitumor effects of immunocytes such as thymus-derived cells (T cells), natural killer (NK) cells, dendritic cells (DCs), and macrophages and immunological factors produced by immunocytes; 37 – 39 2) a large amount of unmethylated dinucleotide repeat sequences present in the nuclei of Lactobacillus can activate the innate immune response by binding to a specific receptor that exists on the surface of human cells; 40 3) Lactobacillus that is suitable for reproduction and growth in an anaerobic environment can selectively accumulate in the hypoxic zones of solid cancers; 41 and 4) Lactobacillus can selectively locate to solid cancers and can be used as a vector for gene therapy and targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Geniposide (purity >99.9%) was obtained from National Institute for the Control of Pharmaceutical and Biological Products (Jilin, China) and diluted with phosphate‐buffered saline (PBS) to a concentration of 5 mg/mL. According to previous literature, [ 33 ] we treated the cells with a concentration of 50 μg/mL geniposide. However, the 50‐μg/mL geniposide treatment had no obvious effect on medulloblastoma cell viability.…”
Section: Methodsmentioning
confidence: 99%
“…To the best of our knowledge, few data have been generated about the effects of probiotics in oral cancer development. Of note, the results of a previous study demonstrated that the administration of Lactobacillus rhamnosus GG (LGG) was able to increase the effects of geniposide, an anticancer molecule tested on human oral squamous carcinoma cells (HSC-3), demonstrating the beneficial role of LGG as potential adjuvant of geniposide treatment (58).…”
Section: Association Of Oral Dysbiosis With Oral Cancer Development (mentioning
confidence: 99%
“…Few data are available on the effects of probiotics on oral cancer. In a recent study, HSC-3 OSCC cell lines were used to determine the effects of Lactobacillus rhamnosus GG (LGG) in increasing the antiblastic effects of geniposide, a derivate of Gardenia jasminoides which in preclinical studies showed important anticancer effects (58,195). The results obtained by the authors showed that the combined treatment with geniposide and LGG increased the apoptotic rate of HSC-3 cells.…”
Section: Anti-tumoral Effects Of Probioticsmentioning
confidence: 99%